2020
DOI: 10.1017/ice.2020.1223
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-onset Clostridioides difficile infections during the COVID-19 pandemic

Abstract: To the Editor-Clostridioides difficile infection (CDI) is the most common healthcare-associated infection in the United States. 1 CDI affects 13 in every 1,000 patients, and~75% of cases are classified as hospital onset. Antimicrobial stewardship and compliance with hand hygiene and personal protective equipment (PPE) protocols are paramount in efforts to reduce horizontal CDI transmission. 2 As an epicenter of the coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus-2 (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 3 publications
4
43
1
1
Order By: Relevance
“…Even though the probability of this has always been regarded as high and has been speculated upon [34], the high rate of CDI and COVID-19 coinfection still remains unproven. We acknowledge that the findings of our study are in contrast to other recent publications, one of which reported a lower incidence of CDI [21], while another a similar incidence of CDI [20] among patients with SARS-CoV-2 infection. The universal use of personal protective equipment (PPE), including gowns and gloves, can account for a diminished rate of CDI coinfection.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Even though the probability of this has always been regarded as high and has been speculated upon [34], the high rate of CDI and COVID-19 coinfection still remains unproven. We acknowledge that the findings of our study are in contrast to other recent publications, one of which reported a lower incidence of CDI [21], while another a similar incidence of CDI [20] among patients with SARS-CoV-2 infection. The universal use of personal protective equipment (PPE), including gowns and gloves, can account for a diminished rate of CDI coinfection.…”
Section: Discussioncontrasting
confidence: 99%
“…The studied cohort from Detroit Medical Center from March 11 th -April 22 nd 2020 was composed of elderly females with SARS-CoV-2 infection. Two other reports [20,21] have presented contradictory findings: a decreased number of cases and a stable number of cases compared to the pre-pandemic era. It is possible that the problem of CDI in COVID-19 patients is underestimated.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…An interesting retrospective cohort analysis from New York, NY compared a pre-COVID-19 cohort of all adult patients diagnosed with CDI with a cohort during the COVID-19 pandemic [ 9 ]. Overall, hospital onset standardized infection ratios were not different in hospital-onset CDI rate despite a trend toward increased high-risk antibiotic exposure.…”
Section: Incidence and Risks Of CDI With Covid-19mentioning
confidence: 99%
“…Overall, hospital onset standardized infection ratios were not different in hospital-onset CDI rate despite a trend toward increased high-risk antibiotic exposure. There was a trend toward an increased length of stay and a trend toward decreased C. difficile testing volumes, suggesting that patients’ diarrhea and gastrointestinal symptoms could have been attributed to COVID-19 [ 9 ]. A possible explanation could be increased and enhanced infection control measures seen in healthcare facilities during the COVID-19 pandemic.…”
Section: Incidence and Risks Of CDI With Covid-19mentioning
confidence: 99%